Pengaruh Konsentrasi Completion Fluid Terhadap Laju Swelling Clay Pada Sumur Produksi Minyak Bumi - Bramansyah Riswanda; Bahruddin Bahruddin; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In the process of oil production wells maintenance, sometimes it has to face containing mud (clay) formations and this situation can detain the process of well maintenance and damage downhole equipment, especially pumps because of clay swelling. This study intends to determine the concentration effect of completion fluid to clay swelling and determine the optimum completion fluid concentration In this study, KCl and XCD polymer has been chosen as the inhibiting compound of clay swelling. Concentration used is 2%, 4% and 6% for KCl, 2, 3 and 4 ppm for XCD polymer with a ratio between the solution with the clay is 1:8, 1 9 and 1:10. The temperature used is room temperature of 25° C. The results showed that the rate of swelling occurs most rapidly at 2% KCl ratio of 1:8. The phenomenon of swelling clay to a solution of XCD polymer is very small so it can be considered no swelling that occurs, either in 2, 3 or 4 ppm solution of polymer XCDKeywords: clay, swelling, oil producer well, KCl, XCD polymer